2020
DOI: 10.1177/0268580920949724
|View full text |Cite
|
Sign up to set email alerts
|

Work hours, work schedules, and subjective well-being in Korea

Abstract: Korea is well known for long work hours. This study examined the effect of not only the total amount of working time but also work schedules on individuals’ subjective well-being in Korea. Drawing on the 2014 Korean Time Use Survey data, the authors selected currently employed people aged 19–65 and examined the effects of total work hours as well as work schedules on feeling rushed, feeling tired, and life satisfaction. Based on the ordered logistic regression analysis, long work hours were negatively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Studies show that long working hours inhibit the opportunities for recovery necessary to be healthy [ 43 ]. Our findings suggest that working for long hours has detrimental effects on nurses through fatigue, health, and pleasure deprivation which is supported by other studies [ 44 ]. In line with our findings, studies in Iran and Sweden showed that long working hours are associated with burnout [ 45 – 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…Studies show that long working hours inhibit the opportunities for recovery necessary to be healthy [ 43 ]. Our findings suggest that working for long hours has detrimental effects on nurses through fatigue, health, and pleasure deprivation which is supported by other studies [ 44 ]. In line with our findings, studies in Iran and Sweden showed that long working hours are associated with burnout [ 45 – 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have shown that working long hours limits the opportunities for recovery necessary to be healthy and happy [ 6 ]. In addition, it has a detrimental effect on SWB through individuals’ fatigue, health deprivation, and time pressure [ 27 ]. Our study shows that a significant negative correlation exists between working hours and SWB, which proves this again.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have highlighted the importance of working hours in understanding individuals’ job burnout or SWB [ 25 , 27 ], we have a different context. Most of the existing related research has been conducted in Western countries, and rarely have thorough studies been conducted in China, even in Asia [ 27 ]. China has the largest population in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About half were working at 9am, 60% at 10am, and 65% at 11am. It might reflect the fact that women are more likely than men to take care of children in the morning (Song and Lee, 2021). However, at noon, higher proportions of women compared to men were working, 34% and 24% respectively.…”
Section: When People Work: Weekdays Vs Weekendsmentioning
confidence: 99%